Informative Narrative in Social Media of Private TV Channels in Spain: Study of Informative Profiles on Instagram and TikTok - Iglesias Cruz, Ana Zulima; Quintana Paz, Nuria (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
This paper examines the evolution of the content of news profiles on Instagram and TikTok belonging to Antena 3 Television an Telecinco. Though a content analysis, the paper ascertains the primary characteristics of these news profiles over the course of a year. It specifies how the novel creative guidelines for the production of pieces are specified in a new audivosual news narrative that responds to the need of traditional media to establish strategies for de creation of content in their social network profiles.